Physical discipline and children's adjustment: Cultural normativeness as a moderator - Jennifer E. Lansford (2018)
Interviews were conducted with 336 mother-child dyads (children's ages ranged from 6 to 17 years; mothers' ages ranged from 20 to 59 years) in China, India, Italy, Kenya, the Philippines, and Thailand to examine whether normativeness of physical discipline moderates the link between mothers' use of physical discipline and children's adjustment. Multilevel regression analyses revealed that physical discipline was less strongly associated with adverse child outcomes in conditions of greater perceived normativeness, but physical discipline was also associated with more adverse outcomes regardless of its perceived normativeness. Countries with the lowest use of physical discipline showed the strongest association between mothers' use and children's behavior problems, but in all countries higher use of physical discipline was associated with more aggression and anxiety. © 2005 by the Society for Research in Child Development, Inc. All rights reserved.